TANTANGAN GURU DALAM MERANCANG PROGRAM PEMBELAJARAN INDIVIDUAL (PPI) BAGI ANAK BERKEBUTUHAN KHUSUS DI PEKANBARU - Rada Anjelina; Rahayu Ramadhani; Siti Mardiati; Frida Ayu Mawarni Zebua (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to identify the challenges faced by teachers in designing Program Pembelajaran Individual (PPI) for children with special needs in Pekanbaru City. PPI is a learning approach that is specifically designed to suit the unique needs, potential and characteristics of each learner, especially in the context of inclusive education which prioritizes equal access for all children. This research uses a descriptive qualitative method with data collection techniques through in-depth interviews and direct observation of teachers in several special schools (SLB). The results showed that teachers face various challenges, such as the number of children with disabilities exceeding the ideal class capacity, the diversity of student characteristics, limited human resources and infrastructure, lack of active parental involvement, and the gap between pedagogic theory and practice in the field. Despite this, teachers continue to do their best by developing creative, flexible and collaborative learning strategies. This study recommends the need for more concrete support from schools, government and families for the successful implementation of IEP in inclusive education.